Tren Penelitian Dampak Kecanduan Media Sosial Bagi Remaja - Tryas Amanda Putri; Juniar Gasa Nova; Tesa Amilia Putri; Risma Anita Puriani; Rizki Novirson (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Social media provides benefits for teenagers, such as access to information, communication, and entertainment, but it also poses challenges, particularly addiction. This study analyzes its impact on mental health, sleep patterns, social interactions, academic performance, and consumer behavior through a literature review (2021–2025). The findings indicate that social media addiction increases the risk of anxiety, depression, and emotional disorders while also disrupting sleep patterns. Socially, direct interactions decrease, and communication skills decline. Academically, focus on learning weakens, and academic performance declines, while consumer behavior increases due to excessive social media exposure. In conclusion, uncontrolled use has significant negative effects, highlighting the need for proper management strategies.